Physical activity of patients with chronic kidney disease - Marczyk, Klaudia; Berner, Aleksandra; Stencel, Katarzyna; Pękała, Maciej; Olszewska, Anna; Stelmaszak, Karina; Polak, Paulina; Polaszek, Monika; Bogowska, Marta; Matyja, Karolina (Journal of Education, Health and Sport, 2023)
Introduction: The main causes of chronic kidney disease (CKD) are diabetic and hypertensive nephropathy. The incidence of civilization diseases is increasing, which also indirectly affects the increase in the incidence of CKD. The patient’s therapy after the diagnosis should include the care of a multi-specialist therapeutic team that will remove as many restrictions as possible in everyday functioning and ensure a high quality of life. In addition to the selection of individual renal replacement therapy, i.a. physical rehabilitation. Despite the fact that in the course of chronic kidney disease physical activity is impaired by numerous pathophysiological processes, the patient should be encouraged to undertake physical activity in order to reduce the risk of death due to cardiovascular diseases, as well as to eliminate many other adverse health effects of the disease. The following paper aims to analyze the impact of physical activity on CKD patients and the pathophysiological causes of low physical activity in this group of patients and the possibility of implementing rehabilitation as an element of comprehensive therapy. Aim of the study: To review the current literature on the physical activity of patients with chronic kidney disease Materials and Methods: A review of the publications available in PubMed, using the key words „chronic kidney disease”, „psychical activity in chronic kidney disease”, physical activity”, „kidney failure”, „dialysis”, „renal rehabilitation”, „quality of life”